Teacher dispositions in teaching reading implications for professional development of teachers in rural schools - Bustos, Marie Theresa A.P (Alipato : a Journal of Basic Education, 2016)
Access through this link:https://journals.upd.edu.ph/index.php/ali/article/view/5784